EFISIENSI EKONOMI SISTEM TANAM LEGOWO PADI SAWAH STUDI KASUS DI KECAMATAN TOMOHON BARAT KOTA TOMOHON - Djuru Masrib Pandensolang; Vicky Ventje Johan Panelewen; Wenny ., Tilaar (AGRI-SOSIOEKONOMI, 2019)
This study aims to analyze how much profit is gained by applying the Legowo row planting system, analyzing the factors of production that affect rice production by applying the Legowo row planting system, analyzing whetherthe use of production factors allocated by farmers to the Legowo planting system economically already efficient. The study was conducted from January to April 2019 in Tomohon Barat Subdistrict, Tomohon City, North Sulawesi Province. The research location was chosen purposively with the consideration that West Tomohon Subdistrict was the center of rice production in Tomohon City with a total area of 447.40 ha of rice fields ( 52% of the total area of rice fields in Tomohon City). The method used in this study is a survey method in the Kelurahan that has paddy fields in the West Tomohon District with interview techniques to respondent farmers. Determination of the sample is done by quota sampling method as many as 50 people taken from 7 (seven) villages in the District of West Tomohon by considering the area of land and the purpose of farming (commercial farm). The variables to be examined in this study are age, education, business experience, group membership, land area, seeds, fertilizer (Urea, SP36 and NPK), labor (HKSP), production, and price. The results showed that the benefits of lowland rice farming with the application of the legowo planting system, farmers in Tomohon Barat Subdistrict, Tomohon City were not yet maximum and had not yet reached economic efficiency, production factors affecting rice production were land area, seeds, fertilizer (Urea, SP 36 and NPK Phonska) and labor, the use of production factors of land area, fertilizers(Urea, SP 36 and NPK Phonska) have not reached economic efficiency, the use of seed production factors and labor is inefficient.*eprm*